2012
DOI: 10.1021/ol3016463
|View full text |Cite
|
Sign up to set email alerts
|

Epicatechin B-Ring Conjugates: First Enantioselective Synthesis and Evidence for Their Occurrence in Human Biological Fluids

Abstract: Herein, the first enantioselective total synthesis of a number of biologically relevant (-)-epicatechin conjugates is described. The success of this synthesis relied on (i) optimized conditions for the stereospecific cyclization step leading to the catechin C ring; on (ii) efficient conjugation reactions; and on (iii) optimized deprotection sequences. These standard compounds have been subsequently used to elucidate for the first time the pattern of (-)-epicatechin conjugates present in four different human bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 14 publications
(10 reference statements)
0
20
0
Order By: Relevance
“…These metabolites are present in blood and tissues. Major conjugates of (À)-epicatechin in human plasma, bile, and urine were (À)-epicatechin 3 0 -O-sulfonate and (À)-epicatechin 3 0 -O-b-glucuronide after ingestion of 50 mg of (À)-epicatechin by volunteers (Romanov-Michailidis et al, 2012).…”
Section: Absorption Of Proanthocyanidin Oligomersmentioning
confidence: 98%
“…These metabolites are present in blood and tissues. Major conjugates of (À)-epicatechin in human plasma, bile, and urine were (À)-epicatechin 3 0 -O-sulfonate and (À)-epicatechin 3 0 -O-b-glucuronide after ingestion of 50 mg of (À)-epicatechin by volunteers (Romanov-Michailidis et al, 2012).…”
Section: Absorption Of Proanthocyanidin Oligomersmentioning
confidence: 98%
“…Major conjugates of (−)-epicatechin in human plasma, bile, and urine were (−)-epicatechin 3′- O -sulfonate and (−)-epicatechin 3′- O -β-glucuronide after ingestion of 50 mg of (−)-epicatechin by volunteers [ 61 ]. Conjugation of (−)-epicatechin with glucuronic acid had already been observed in human blood brain barrier cell line model [ 62 ].…”
Section: Bioavailability Of Red Wine Phenolicsmentioning
confidence: 99%
“…Romanov-Michailidis et al synthesized the conjugated sulfate and detected it in human biological uids. 22) e product ion spectra of the synthetic sulfate conjugate showed that m/z 231 corresponds to the 3′-or 4′-O-sulfate, and the product ion at m/z 247 corresponds to the 5-or 7-O-sulfate. 23) Compared to previous results, the assignment results for O-methyl-gallocatechin also suggest that a sulfate conjugated to the B-ring is produced.…”
Section: Analysis Of Conjugates Of Green Tea Components In Mouse Urinementioning
confidence: 99%